Probing the inner Galactic halo with blue horizontal-branch stars: Gaia DR3-based catalogue with atmospheric and stellar parameters - Culpan, R.; Dorsch, M.; Geier, S.; Pelisoli, I.; Heber, Ulrich; Kubátová, B.; Cabezas, M. (Astronomy & Astrophysics, 2024)
Context. Stars that are found on the blue horizontal-branch (BHB) evolved from low-mass stars that have completed their core hydrogen-burning main sequence (MS) stage and undergone the helium flash at the end of their red giant phase. Hence, they are very old objects that can be used as markers in studying galactic structure and formation history. The fact that their luminosity is virtually constant at all effective temperatures also makes them good standard candles. Aims. We have compiled a catalogue of BHB stars with stellar parameters calculated from spectral energy distributions (SEDs) constructed using data from multiple large-scale photometric surveys. In addition, we update our previous Gaia Early Data Release 3 (EDR3) catalogue of BHB stars with parallax errors less than 20% by using the SED results to define the selection criteria. The purpose of these catalogues is to create a set of BHB star candidates with reliable stellar parameters. In addition, they provide a more complete full-sky catalogue with candidate objects found along the whole BHB from where RR-Lyrae are found on the instability strip to the extreme horizontal-branch (EHB). Methods. We selected a large dataset of Gaia Data Release 3 (DR3) objects based only on their position on the colour-magnitude diagram (CMD), along with the tangential velocity and parallax errors. The SEDs were then used to evaluate contamination levels in the dataset and derive optimised data quality acceptance constraints. This allowed us to extend the Gaia DR3 colour and absolute magnitude criteria further towards the EHB. The level of contamination found using SED analysis was confirmed by acquiring spectra using the Ondrejov Echelle spectrograph, attached to the Perek 2m telescope at the Astronomical Institute of the Czech Academy of Sciences. Results. We present a catalogue of 9172 Galactic halo BHB candidate stars with atmospheric and stellar parameters calculated from synthetic SEDs. We also present an extended Gaia DR3-based catalogue of 22 335 BHB candidate stars with a wider range of effective temperatures and Gaia DR3 parallax errors of less than 20%. This represents an increase of 33% compared to the our 2021 catalogue, with a contamination level of 10%.
CRIS-Team Scopus Importer:2024-05-31
Keywords: Catalogs; Hertzsprung-Russell and C M diagrams; Stars: horizontal-branch